HUBUNGAN ANTARA KESEIMBANGAN KEHIDUPAN KERJA DAN KEPUASAN KERJA: SEBUAH TINJAUAN LITERATUR - Adinda Khoirunnisa Nur; Difani Cahya Prastiwi; Rahma Meilina Arrazi; Netty Merdiaty (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This study examines the relationship between work-life balance and job satisfaction through a literature review. Results indicate a significant positive relationship, where good work-life balance enhances job satisfaction. Conversely, imbalance may decrease satisfaction levels. Factors such as organizational culture, support, and leadership style also influence this relationship. This research provides insights for organizations to improve employee well-being to support performance and productivity.